2019
DOI: 10.1371/journal.pone.0220462
|View full text |Cite
|
Sign up to set email alerts
|

Serum CXCL9 and CCL17 as biomarkers of declining pulmonary function in chronic bird-related hypersensitivity pneumonitis

Abstract: The clinical course of chronic hypersensitivity pneumonitis (HP) with fibrosis is similar to that of idiopathic pulmonary fibrosis (IPF). Current research is expected to identify biomarkers effective in predicting the deterioration of lung function in a clinical setting. Our group analyzed the relationships between the following parameters in chronic bird-related HP: patient characteristics, serum markers, lung function, HRCT findings, BALF profiles, and the worsening of lung function. We also analyzed serum l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 34 publications
1
22
1
Order By: Relevance
“…Eosinophil is one of the Type 2 immune components. As previously reported, T2 immunity is activated in some ILD patients [30,31]. Among the patients in this study, EOP ratios were within normal ranges both before and after treatment.…”
Section: Discussionsupporting
confidence: 85%
“…Eosinophil is one of the Type 2 immune components. As previously reported, T2 immunity is activated in some ILD patients [30,31]. Among the patients in this study, EOP ratios were within normal ranges both before and after treatment.…”
Section: Discussionsupporting
confidence: 85%
“…High-sensitivity CRP previously has been found to be elevated in HP in other bivariate analyses [33,34]. Although we did not find as association with KL-6, this has been observed in in other studies of HP [33][34][35]. Estimated alveolar NO differed statistically in bivariate analysis, but not in multivariate modelling.…”
Section: Discussioncontrasting
confidence: 70%
“…CXCL9 is an IFN-γ-inducible chemokine that is released by neutrophils, 25 , 34 and serve as Th1-type inflammatory markers in respiratory diseases. 35 , 36 When compared to healthy controls, CXCL9 concentrations were increased in COPD patients and positively correlated with markers of neutrophilic airway inflammation. 26 Fulkerson et al demonstrated that CXCL9 inhibits eosinophil migration to the lungs of allergen-induced mice.…”
Section: Discussionmentioning
confidence: 99%